Species diversity, carbon stock of above ground biomass and biomass decomposition of secondary tropical forest in UNIMAS, Kota Samarahan, Sarawak - Aman, Nurafiza (Universiti Malaysia Sarawak (UNIMAS), 2015)
Tropical secondary forest extensively increasing as the forest area coverage widen up every year, which mainly caused by human activities (logging, land clearing, shifting cultivation). By the existence of secondary forest, it may helps in contributing to mitigate climate change effect due to its richer species composition that potentially in carbon storing and sequestrating. This study was mainly to provide information on species diversity, estimated above ground biomass (both trees and herbaceous vegetation) and biomass decomposition in UNIMAS, Kota Samarahan, Sarawak, Malaysia. In one hectare study area, tree species has a total of 920 individuals from 164 species, 101 genera and 42 families. The herbaceous plants have 34 species from 34 genera and 27 families. The estimated total above ground biomass (TAGB), carbon stock and carbon sequestration are 108.16 Mg ha-1, 50.84 Mg C ha-1 and 5.32 Mg C ha-1 yr-1, respectively. Estimated dry above ground biomass and carbon stock of herbaceous plants were 2.4 × 10-3 Mg m-2 and 1.2 × 10-3 Mg ha-1, respectively.